2011
DOI: 10.1016/j.juro.2011.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Complication Rates of Ureteroscopic Lithotripsy in Children: Results of Multi-Institutional Retrospective Analysis by Pediatric Stone Disease Study Group of Turkish Pediatric Urology Society

Abstract: Semirigid ureteroscopy is effective, with a 90% stone-free rate and efficacy quotient. Most complications are low grade and self-limiting. Our results confirm that prolonged operative time is an independent predictor of complications, and should be considered when choosing and performing the treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 29 publications
1
52
1
4
Order By: Relevance
“…The stone free rate was 92.8%, and complications occurred in 8.4% of the cases (54 of 642), which were mostly low grade and self-limiting. Multivariate analysis showed that operation time was the only statistically significant parameter affecting the complication rate (25). These studies show us that laser lithotripsy is widely and successfully applied in the treatment of pediatric ureteral calculi with minimal morbidity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The stone free rate was 92.8%, and complications occurred in 8.4% of the cases (54 of 642), which were mostly low grade and self-limiting. Multivariate analysis showed that operation time was the only statistically significant parameter affecting the complication rate (25). These studies show us that laser lithotripsy is widely and successfully applied in the treatment of pediatric ureteral calculi with minimal morbidity.…”
Section: Discussionmentioning
confidence: 62%
“…(4) In this manner, SWL and URS are recommended as the first-line treatment modality in the EAU guidelines (26). Furthermore, although pediatric ureter is much more dynamic than its adult counterpart, which means that SWL should be applied before URS, there are a lot of centers which directly apply URS rather than SWL for pediatric ureteral stones (13,25). This brings up the fact that URS might become more and more popular in the treatment of pediatric ureteral stone disease, and may even be considered as the first-line treatment modality rather than SWL in the future.…”
Section: Introductionmentioning
confidence: 99%
“…According to EUA pediatric guidelines at the present time, while first-line treatment option in stones smaller than 1 cm is flexible URS, first-line treatment option in stones larger than 1.5 cm is PCNL (1,2). PCNL may present problems in infants and preschool-age children due to the small size and mobility of the pediatric kidney, friable renal parenchyma, and the small size of the collecting system.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, PNL is considered to be a safe method for protecting the renal tissue in the growth period. However, a prolonged duration of surgery for getting stone-free patients leads to an increased number of complications (14). The primary major complication of PNL technique is organ injury.…”
Section: Discussionmentioning
confidence: 99%